2017
DOI: 10.1038/nclimate3234
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of solar brightening to the US maize yield trend

Abstract: Predictions of crop yield under future climate change are predicated on historical yield trends 1-3 , hence it is important to identify the contributors to historical yield gains and their potential for continued increase. The large gains in maize yield in the US Corn Belt have been attributed to agricultural technologies 4 , ignoring the potential contribution of solar brightening (decadal-scale increases in incident solar radiation) reported for much of the globe since the mid-1980s. In this study, using a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 44 publications
1
69
0
Order By: Relevance
“…A previous study suggested the solar brightening during GFP is responsible for about 27% of the observed increase in US maize yield from 1984 to 2013 (Tollenaar et al., ). However, we did not find a significant increase in solar radiation across the four corn states considered during the study period when using the same solar radiation dataset integrated over the grain filling period (Supporting Information Figure S6).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A previous study suggested the solar brightening during GFP is responsible for about 27% of the observed increase in US maize yield from 1984 to 2013 (Tollenaar et al., ). However, we did not find a significant increase in solar radiation across the four corn states considered during the study period when using the same solar radiation dataset integrated over the grain filling period (Supporting Information Figure S6).…”
Section: Resultsmentioning
confidence: 98%
“…The weekly reported area ratios were interpolated using sigmoid function. The target phenological stages (emerged, silking, dent, and mature stages) were then determined as the date when the interpolated area ratio reached 50% on a state level (Tollenaar et al., ). The phenological dates from CPR were used as a reference to evaluate the MODIS‐based estimations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various approaches have been used to quantify the impact of global dimming. A popular approach is to quantify agroecosystem productivity, crop yields, in response to incident global radiation and diffuse radiation fraction changes by using historical climate and crop yield data (Lobell & Asner, 2003;Proctor et al, 2018;Tollenaar et al, 2017;Yang et al, 2013;Zhang, Li, Yue, & Yang, 2017), but these results were usually beset by the collinearity among climate variables (especially among solar radiation, temperature, precipitation ;Lobell & Burke, 2009;Lobell, Schlenker, & Costa-Roberts, 2011). Other studies on GPP or NPP of natural ecosystems (Cirino, Souza, Adams, & Artaxo, 2014;Rap et al, 2015;Urban et al, 2012) and agroecosystems (Niyogi et al, 2004;Xin et al, 2016) in response to diffuse radiation are based on flux measurements using eddy covariance techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no evidence of this occurring in maize, as 4 to 18 yr of unchanging yields need to be recorded before yield plateaus become statistically significant (Grassini et al, 2013), it is quite possible that maize yields in the United States and Canada are experiencing or are nearing a plateau (Lobell and Azzari, 2017). Solar brightening is responsible for 27% of the on‐farm maize yield gains in the US Corn Belt observed between 1984 and 2013 (Tollenaar et al, 2016), calling into question the true contribution of genetic improvement during this timeframe. Concurrent with solar brightening is increases in the variation in GY observed both within and between fields (i.e., heterogeneity), with average yield differences more than doubling between the worst and best soils since 2000 (Lobell and Azzari, 2017).…”
mentioning
confidence: 99%